THE EFFECTIVENESS OF GUIDED DISCOVERY LEARNING TO TEACH INTEGRAL CALCULUS FOR THE MATHEMATICS STUDENTS OF MATHEMATICS EDUCATION WIDYA DHARMA UNIVERSITY - Yuliana Yuliana; Tasari Tasari; Septiana Wijayanti (Jurnal Infinity, 2017)
The objectives of this research are (1) to develop Guided Discovery Learning in integral calculus subject; (2) to identify the effectiveness of Guided Discovery Learning in improving the students’ understanding toward integral calculus subject. This research was quasy experimental research with the students of even semester in Mathematics Education Widya Dharma University as the sample. Cluster Random sampling was conducted to determine control group that was taught using Conventional model and experimental group that was taught using Guided Discovery Learning model. The instruments of this research included pre-test, post-test, and student’s response questionnaire. The data of post-test was analyzed using T-test. The result was H0 was rejected for the level of significance The result of this data analysis found out that Guide Discovery Learning was more effective than Conventional Model. It was supported by the result questionnaire. The result of questionnaire that  more than 75% questionnaire items got 67.65% positive response. It means Guided Discovery Learning can increase students’ interest in joining integral calculus class.